LITERARY TRANSLATION: VIETNAMESE TRANSLATORS’ CHOICES OF SOURCE MATERIALS = DỊCH VĂN HỌC: CÁCH LỰA CHỌN TÁC PHẨM GỐC CỦA DỊCH GIẢ VIỆT NAM - Vũ, Thị Phương Quỳnh (2020)
Selection of source materials- the very first step in the translation process performs a key role in literary translation, and deserves serious concern. Various scholars have mentioned the significance of material selection in literary translation; yet, virtually no indepth studies about choices of source materials have been carried out so far. This study attempted to provide a thorough analysis of Vietnamese translators‟ selection of source materials, with a view to explicating their patterns of choices, as well as the motivations behind those choices. Five Vietnamese translators and their translations were chosen as subjects of this study. Semi-structured interview was adopted as the research method. Motivations behind materials selection based on theories offered by Landers (2001) and Jones (2009) included three individual factors and four social factors. The chosen translators demonstrated completely different tendencies in choosing source materials; however, they had in common the factors influencing those choices. As for individual factors, translator‟s ethics and translator‟s ideology were the most dominant, while translation production team and communities of interest stood out as the most noticeable social factors affecting Vietnamese translators‟ materials selection.